How networking and collaboration helps make agriculture work for women - Hosenally, Nawsheen (Technical Centre for Agricultural and Rural Cooperation, 2018)
Pioneers who have been engaging women in agribusiness share their experiences and perspectives on why networking is important for women agripreneurs.